Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1074/jbc.m114.592139
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the Collagen-specific Molecular Chaperone Hsp47 Causes Endoplasmic Reticulum Stress-mediated Apoptosis of Hepatic Stellate Cells

Abstract: Background: Although knockdown of heat shock protein 47 (Hsp47) attenuates liver fibrosis, the underlying molecular mechanism is unknown. Results: Deletion of Hsp47 caused activated hepatic stellate cells (HSCs) to undergo ER stress-mediated apoptosis when autophagy was inhibited. Conclusion: ER stress-induced apoptosis may underlie the clearance of collagen-producing HSCs. Significance: Hsp47 could be an attractive therapeutic target for fibrosis treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 50 publications
1
60
0
Order By: Relevance
“…One mechanism by which this can occur is HSC apoptosis . Induced nonphysiological ER stress in HSCs was shown to be antifibrotic, attributed to induction of cell death in cultured HSCs . We observed increased UPR signaling in siTANGO1 cells, and increased expression of CHOP and DR5, genes involved in UPR‐mediated apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…One mechanism by which this can occur is HSC apoptosis . Induced nonphysiological ER stress in HSCs was shown to be antifibrotic, attributed to induction of cell death in cultured HSCs . We observed increased UPR signaling in siTANGO1 cells, and increased expression of CHOP and DR5, genes involved in UPR‐mediated apoptosis.…”
Section: Discussionmentioning
confidence: 72%
“…This work builds upon previous efforts to recreate chronic ER stress in fish larvae (Cinaroglu et al, 2011), and to elicit chronic ER stress in mammals by overexpression of misfolded ER client proteins or deletion of ER chaperones (e.g., [Ji et al, 2011; Zode et al, 2011; Kawasaki et al, 2015]). We have used this system as a tool to probe how UPR signaling becomes altered during persistent and/or repeated activation.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicated that HSP47 may be a potential therapeutic target in LSCC and indirectly supported the concept that low HSP47 expression is correlated with short survival and poor prognosis in LSCC. As shown in previous studies, HSP47 plays an important regulatory role in various types of tumours (39)(40)(41) and has a close relationship with tumour apoptosis (40,42). However, the mechanism of HSP47-mediated Hep-2 cell apoptosis is still unknown.…”
Section: Discussionmentioning
confidence: 99%